X-ray and electron diffraction studies in materials science - Dyson, D. J. (David John) (Maney for the Institute of Materials, Minerals and Mining, 2004)
X-ray diffraction was first applied almost a century ago. The subsequent development of the technique and its application across industry and academia to physical, chemical and biological problems has made it an important tool in the armoury of the analyst. Much of he early work developed the basic theory and much of this is still relevant today. These early years saw the publication of some extremely good texts on the subject. Much of what is presented in these is still applicable; many of them however are no longer in print. More recent times have seen the emergence of diffractometry an control systems based on the PC, driven by commercial software, complemented by the development of new techniques to address the demands of product charaterisation. Fully validated, the use of this software places less demands on the user and some of the crystallographic basis of data collection, reduction and interpretation is lost. The demands throughout and quality are not always consistent, and international trade has introduced accreditation issues. Experience has become a vital part of the success of XRD. This book addresses the requirements of the analyst working in a materials laboratory from a practical angle providing .reference where necessary to more detailed work. It also attempts to show the link between XRD and other analytical techniques with integral diffraction facilities. Some applications are briefly discussed to show what can be achieved; other to show what to look for and what to check. The provision of computing facilities, while having many benefits, can also lead to a false reliance in the output that they generate. The importance of the errors that can occur, how to handle them and need to provide some measure of uncertainty to the customer are considered. It is based on the use of crystallography over a period of forty years in an industrial laboratory. The author believes that there is a need to make the users of the technique more aware of what the computer is doing. Without this the interpretation of results and the operator imput can be at risk. The current introduction of quaity standards, e.g. ISO 17025, to provide a base for assuring product integrity should now direct analysts approach.